Regulation Mechanism for Friction Coefficient of Poly(vinylphosphoric acid) (PVPA) Superlubricity System Based on Ionic Properties - Mengmeng Liu; Lihui Wang; Caixia Zhang; Yanhong Cheng; Congbin Yang; Zhifeng Liu (Nanomaterials, 2022)
Adjustable lubrication aims to achieve active control of the relative motion of the friction interface, providing a new idea for intelligent operation. A new phenomenon of sudden changes of friction coefficient (COF) in the poly(vinylphosphoric acid) (PVPA) superlubricity system by mixing different lubricants, was found in this study. It was found that anions were the critical factor for the COF change. The change degrees of the COF were investigated by a universal micro tribometer (UMT). A quartz crystal microbalance (QCM)-D was used to analyze the adsorption quantity of anions on the PVPA surface. The hydratability of the PVPA interface was controlled by changing the anionic properties (the amount of charge and structure), thus regulating the COF. The adsorption difference of anions is an important reasoning of how anionic properties can regulate the hydratability. It was analyzed by molecular dynamics simulation. For anions carrying different numbers of charges or double bonds, the adsorption quantity of anions was mainly affected by the adsorption degree on the PVPA surface, while the adsorption quantity of anions with different molecular configuration was synergistically regulated by the adsorption degree and adsorption area of anions on the PVPA surface. This work can be used to develop smart surfaces for applications.